The temporariness of Bangladeshi migration in Greece - Minamide, Kazuyo (Migration Letters, 2021)
Bangladeshi overseas workers migrating to the West, who once aimed to establish long-term prospects, have been increasingly relying on temporary migration since the mid-2000s, as a result of changes in the migration policies and economic conditions of destination countries and corresponding shifts in migrant strategies. This paper examines the “temporariness” of low-skilled Bangladeshi migrant workers in Greece, by comparing the experiences of those who arrived in the 1990s and were issued resident permits with those who arrived in the mid-2000s with the support of the former immigrants, but who have not been able to secure any kind of visa. Members of the first generation have been forced to shorten their long-term stays and shift to temporary migration, while members of the second generation have had to suspend their lives in a state of extended temporariness. Despite these challenges, the enduring positive image of overseas migration in villages in Bangladesh allows migrants to maintain their motivation and they, therefore, continue to promote the migration culture.